The effect of education policy on crime: An intergenerational perspective - Costas Meghir; Mårten Palme; Marieke Schnabel (Institute for the Study of Labor (IZA), 2011)
A number of studies have shown that education reforms extending compulsory schooling reduce criminal behavior of those affected by the reform. We consider the effects of a major Swedish educational reform on crime by exploiting its staggered implementation across Sweden. We first show that the reform reduced crime rates for the generation directly affected by the reform. We then show that the benefits extended to the next generation with large reductions in the crime rates of the children of those affected. The effect operates only through the father and points in the direction of improved parenting rather than resources.
urn:nbn:de:101:1-2012010913628
Keywords: I20; I21; I28; K42; N34; 330; comprehensive school; economics of crime; returns to education; returns to human capital; Schulpolitik; Humankapital; Bildungsertrag; Generationenbeziehungen; Kriminalitätsökonomik; Schweden